Economía Ambiental como elemento para el Desarrollo de la Asociación de Productores Lácteos LLAFRAK - Fernández-Rodríguez, Marcela (2019)
In the North Region of Costa Rica, there is a large number of small agro-industries composed by one or more partners that provide with resources, but begin with little knowledge on good practices in transformation processes or administrative management that includes the economic issue from the environmental perspective. The producer association LLAFRAK is a small dairy processing plant, located in Juanilama de Pocosol, where 10 partners deliver their dairy production to produce cheese, yogurt and sour cream. Currently, they have developed some improvements in their processes, however they still have many shortages by the lack of resources. This research article, through an analysis of the current situation of this small business, to determine the positive and negative externalities that will define the potential for the development of the company within the socio-economic context of the region. After the corresponding analysis it is concluded that the company has great potential for growth, since its negative externalities can be solved in medium term, generating strengths that will allow them to initiate a process of continuous improvement and expansion at regional, national and international level.